2021
DOI: 10.1111/pde.14540
|View full text |Cite
|
Sign up to set email alerts
|

The link between hidradenitis suppurativa and phylloid hypomelanosis in partial trisomy‐13 mosaicism: New evidences and further genetic/pathogenetic insights

Abstract: Partial trisomy‐13 mosaicism (PT13M) is a rare condition. Among its possible associated cutaneous features, phylloid hypomelanosis (PH), characterized by leaf‐like macules reminiscent of floral ornaments in the form of round or oval spots and patches and oblong lesions, is typical. Two cases of PH associated with hidradenitis suppurativa (HS) have been already reported in the literature. We report a third child with PH due to PT13M associated with HS‐like lesions limited to hypomelanotic regions. We hypothesiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…The young age at presentation in our case further supports the hypothesis that the chromosomal duplication in trisomy 13 directly contributes to follicular occlusion. Though several mechanisms have been suggested, no genes on chromosome 13 have been linked causally with follicular occlusion 5 . The patient's partial response of his skin disease to immunoglobulin replacement therapy suggests that the dysregulation of the immune system may contribute to this disease phenotype in these patients, especially in light of data that have shown that microbiome dysbiosis may be associated with HS 6 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The young age at presentation in our case further supports the hypothesis that the chromosomal duplication in trisomy 13 directly contributes to follicular occlusion. Though several mechanisms have been suggested, no genes on chromosome 13 have been linked causally with follicular occlusion 5 . The patient's partial response of his skin disease to immunoglobulin replacement therapy suggests that the dysregulation of the immune system may contribute to this disease phenotype in these patients, especially in light of data that have shown that microbiome dysbiosis may be associated with HS 6 .…”
Section: Discussionmentioning
confidence: 99%
“…The patient's partial response of his skin disease to immunoglobulin replacement therapy suggests that the dysregulation of the immune system may contribute to this disease phenotype in these patients, especially in light of data that have shown that microbiome dysbiosis may be associated with HS 6 . The success of Inoue et al 5 in using IVIg as treatment further supports this potential contributory pathogensis 4 . It has also been suggested that the gap junction β2 gene in connexin 26 on chromosome 13 may contribute to follicular occlusion through yet unknown mechanisms 7 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation